Kajian Kelengkapan Administrasif, Farmasetik, dan Klinis Pada E-Resep Pasien di Puskesmas Petir Kota Tangerang Januari – Maret 2023 - widyapratiwi, Ritha; Febriani, Amelia; Husna, Fadia (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2025)
The completeness of prescription review must be carried out to prevent the occurrence of medication errors in e-prescription services. This study aims to determine the results of the study of the completeness of outpatient e- prescriptions for general poly patients at the Petir Public Health Center Tangerang City. This type of research is descriptive with a cross sectional approach and retrospective sampling with a total sample of 330 e- prescriptions. The results showed the completeness of the e-prescription administration in the patient's name 100%, age 100%, gender 100%, weight 99.70%, doctor's name 100%, doctor's SIP 56%, doctor's paraf 100%, and date of prescription writing 100%. In pharmaceutical terms, the dosage form 96.06%, dosage strength 98.48%, quantity of drugs 100%, rules and methods of use 97.27%, and incompatibility 100%. In clinical terms, the accuracy of dosage 88.18% and the potential for drug interactions 34.24% ,with 38.64% low interaction potential and 61.36% moderate interaction potential . It is hoped that the results of this study will encourage doctors and pharmacists to pay more attention to the completeness of e-prescriptions, thereby improving the service to patients, ensuring that treatment is adhered to and preventing medication errors in e-prescribing.